Effect of Pulsed Electric Field on the Cations Removal from Salt-Affected Soils to Optimize Energy Use Efficiency in Reclamation - Ahmed Abou-Shady (Resources)
In arid and semi-arid zones, reclaiming/restoring salt-affected soil is considered a significant challenge because of the limited amount of water available for soil washing. The reclaimed salt-affected soil is regarded as a valuable resource for increasing the production of food and feed. In the current study, soil electrokinetics (SEK) under pulsed-mode electric field operation was used to evaluate and optimize energy use efficiency for reclaiming salt-affected soils, which is one of the electro-agric technology branches that was suggested in 2021 to address the water crisis in arid and semi-arid regions. Under a fixed applied voltage of 5 V, or 1 V/cm, the calcareous, highly salinized soil under investigation was reclaimed. A 25% reduction in applied voltages with time OFF set at 15, 30, 60, and 120 min and a 50% reduction with time OFF set at 15, 30, 60, and 120 min were the two pulsed electric field techniques that were examined. The findings demonstrated that the removal of Na+ surpasses half (50%) in the majority of pulsed-mode studies. By decreasing the removed K+, which is crucial for plant growth, the pulsed modes of electric fields 25 and 50% showed an economic advantage over the control experiment, which operated with a continuous electric field. Throughout the control experiment, very little Ca2+ was removed. However, the amount of Ca2+ removed rose when the electric field’s pulsed mode was applied, and the removal percentages were higher for the pulsed 50% strategy than the pulsed 25% strategy. In nearly every segment of every experiment (control, pulsed 25%, and pulsed 50%), the pH levels exceeded the initial value of 8.05. The pulsed 25% strategy of the OFF time showed an improvement in current passing at the longest interval of 120 min; the pulsed 50% strategy of the OFF time showed an improvement in current passing at the shorter and longer intervals of 15, 60, and 120 min; however, the interval of 30 min had a negative effect. The cumulative EO flow at the time OFF interval of 60 min was improved by the pulsed 25% strategy throughout the first seven days of operation, and by the end of the trial, the control experiment exhibited high values. The highest values, however, were displayed by the pulsed 50% field at the time OFF interval of 60 min. The anolyte pH decreased for the majority of the time OFF intervals over the first seven days of the trial for both the 25% and 50% pulsed strategies. Lastly, in order to minimize the overall energy consumption, it is strongly advised that the pulsed mode of the electric field be used while reclaiming salt-affected soil.